Pengaruh Laba Akuntansi dan Arus Kas Terhadap Return Saham Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Panjaitan, Jordan Elifantino (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This research aims to investigate the influence of accounting profit and cash flow on the stock returns of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The study utilizes historical data from several manufacturing firms to analyze the relationship between accounting profit, cash flow, and stock returns. The findings indicate that both accounting profit and cash flow have a positive and significant impact on stock returns. Performance parameters such as profit and cash flow are considered important by investors and creditors when assessing company performance and making investment decisions. This research also supports the notion that information regarding profit and cash flow can serve as good indicators for predicting future stock returns.